Physiological responses in mice to levamisole - YUVARAJ, N; RAMNATH, V (The Indian Journal of Animal Sciences, 2014)
Levamisole is widely used as a broad-spectrum anthelmintic and immunopotentiator. The present study was undertaken to evaluate the combined physiological and immunopotentiating responses of levamisole in normal mice and to compare and grade the efficacy of levamisole over immunosuppressive drug such as cyclophosphamide. The haematological paraneters such as haemoglobin concentration and total erythrocyte count did not var much by levamisole asministration, pararneters such as haemoglobin concentration and total cruthrocyte count did not vary much by leavmisole administration, whereas, relative organ weirghts of thymus and spleen, bone marrow celularity, phagocytic activity of peritoneal macrophages, total tecocyte count and in vitro proliferation of splenocytes were quite significantly enhonced by levamisole administration. On the other hand, cyclophophamide suppressed all the haematological paramenter and relative weights of lymphoid organs significantly. Levamisole could trigger the immune defense-shield of the body by increasing the functions of lymphoid organs such as thymus and spleen, causing increased proliferation of bone marrow stem cells and by stimulating the phagocytic functions of macrophages without casing any marked side effect on haematopoietic system.Â